MOF‐Derived Oxygen Vacancy‐Rich Co/CoO@NC‐CNTs Hybrid Electrocatalyst for Oxygen Reduction Reaction. Issue 3 (18th January 2023) - Guo, Xinjie; Gan, Xingyu; Wang, Yun; Lv, Xiaoxia; Wang, Fengxiang; Wang, Shuxin; Peng, Shan
Abstract: Low‐cost and high‐efficiency oxygen reduction reaction (ORR) electrocatalysts are the basis for large‐scale applications of electrochemical energy storage and conversion technologies such as fuel cells and metal‐air batteries. Herein, cobalt and oxygen vacancy‐rich cobalt oxide encapsulated in nitrogen‐doped carbon and carbon nanotubes (Co/CoO@NC‐CNTs) have been prepared by direct solid‐state pyrolysis of Co‐MOF. The carbon morphology, oxygen vacancy content and type of nitrogen can be finely tuned by mixing Co‐MOF with proper amounts of melamine. The optimized material has an interwoven CNT structure with abundant micro‐ and mesopores, suitable nitrogen type and certain number of oxygen vacancies and exhibiting outstanding ORR electrocatalytic performance in alkaline media with an onset potential of 0.96 V and a half‐wave potential of 0.88 V vs RHE, which is higher than 20 wt% Pt/C, as well as being highly stable and well resistant to methanol. Abstract : A Co/CoO@NC/CNT‐10 catalyst was effectively synthesized using melamine‐assisted pyrolysis with Co‐MOF as the precursor. With the synergistic effect of metal species, oxygen defects and N‐doped carbon nanotubes, the intrinsic activity and electron transfer ability of the catalysts were greatly improved, showing excellent electrocatalytic oxygen reduction performance.